Implantable cardioverter-defibrillator therapy for primary prevention of sudden death after alcohol septal ablation of hypertrophic cardiomyopathy - Cuoco, Frank A; Spencer, 3rd, William H; Fernandes, Valerian L; Nielsen, Christopher D; Nagueh, Sherif; Sturdivant, J Lacy; Leman, Robert B; Wharton, J Marcus; Gold, Michael R (Journal of the American College of Cardiology, 2008)
The purpose of this study was to examine the effects of alcohol septal ablation (ASA) on ventricular arrhythmias among patients with obstructive hypertrophic cardiomyopathy (HCM), as measured by appropriate implantable cardioverter-defibrillator (ICD) discharges. Alcohol septal ablation is an effective therapy for patients with symptomatic HCM. However, concern has been raised that ASA may be proarrhythmic secondary to the iatrogenic scar created during the procedure. The impact of ASA on ventricular arrhythmias has not been well described. This prospective study included 123 consecutive patients with obstructive HCM who underwent ASA and had an ICD implanted for primary prevention of sudden cardiac death (SCD). The ICDs were implanted based on commonly accepted risk factors for SCD in the HCM population. Data from ICD interrogations during routine follow-up were collected. Nine appropriate ICD shocks were recorded over a mean follow-up of 2.9 years in the cohort, which had a mean of 1.5 +/- 0.9 risk factors for SCD. Using Kaplan-Meier survival analysis, the estimated annual event rate was 2.8% over 3-year follow-up. There were no significant differences in the incidence of risk factors between patients who did and did not receive appropriate shocks. The annual rate of appropriate ICD discharges after ASA is low and less than that reported previously for primary prevention of SCD in HCM. This suggests that ASA is not proarrhythmic. Traditional SCD risk factors did not predict ICD shocks in this cohort.